Structural Funds and the 1992 Program in the European Community - Gordon, James (IMF Working Papers; Working Paper ;, 1991)
Equity and efficiency justifications are found for the Community's Structural Funds which are discovered to be carefully targeted at depressed regions, albeit with some horizontal inequities. If Fund transfers displace national assistance, then they may be misallocated by being tied to regional indicators. The recent doubling in size enhances the Funds' ability to assist losers from the creation of a single European market in 1992. However, they fall short of constituting a safety net since they provide little automatic assistance to regions suffering negative shocks. Compensation of losers from the 1992 program would require an overhaul of the present allocation system, if not a further increase in scale.